Discursive seams about work in textile factions in the city - da Costa, Greciely Cristina; Chiaretti, Paula (Árboles y Rizomas, 2023)
This article analyzes current work practices and discourses about and of work based on the documentary “Estou me guardando pra quando o carnaval chegar” (2019) by Marcelo Gomes. In this documentary, we observed, through the discursive functioning of the images (Costa, 2018) and statements by the workers, how the textile work, which is carried out at home, displaces historical work practices, including the space of intimacy and leisure, in order to occupy the city entirely, and thus its name of “work city”. At least until carnival arrives.
Keywords: discourse; work; space-time; neoliberalism; images